Harmonizing Aesthetics and Psychological Well-being: An Indepth Exploration of the Integrative Impact of Dysport in Cosmetic Procedures - Nikandish, Mehrasa; Nikandish, Mohammad; Behnoud, Hedayatpour (European Scientific Journal, ESJ, 2024)
This research endeavors to delve into the intricate interplay between aesthetic intelligence, aesthetic sensitivity, and psychological well-being within the framework of positive psychology. Recognizing the profound influence of environmental aesthetics on individuals’ health and well-being, this study aims to illuminate the relationship between aesthetic intelligence and psychological well-being, with aesthetic sensitivity acting as a mediating factor. Employing a correlational research design, structural equation modeling was applied as the methodological approach. The research cohort comprised all students enrolled at Bu-Ali Sina University during the academic year 2018-2019. Employing cluster sampling, 384 students were selected based on the recommended sample size for structural equation modeling. The instruments employed in this study included the Ryff Well-being Scale (2), the Aesthetic Intelligence Scale developed by Rashid et al. (2017), and Abdulsalami’s (2013) Aesthetic Sensitivity Scale. The findings derived from structural equations analysis revealed that both aesthetic intelligence and aesthetic sensitivity exerted a significant direct impact on psychological well-being. Furthermore, aesthetic intelligence demonstrated a direct and significant effect on aesthetic sensitivity. The exploration of indirect relationships indicated that aesthetic intelligence, acting through the mediation of aesthetic sensitivity, significantly influenced psychological well-being. Considering these outcomes, it can be inferred that individuals’ awareness and appreciation of environmental beauty positively contribute to their psychological well-being. Consequently, the development of educational programs aimed at enhancing aesthetic capabilities in individuals holds the potential to elevate overall well-being.